Islamic Scholar Leadership in the Modernization of Pesantren Management - Zainab, Iin; Suhermanto, Suhermanto (AFKARINA: Jurnal Pendidikan Agama Islam, 2023)
This paper aims to analyze and examine the role of the kiai as the head of an Islamic boarding school (pesantren) in modernizing its management practices to ensure the achievement of the institution's vision and mission. The study uses a qualitative research methodology with a case study approach, collecting data through observation, interviews, and documentation, and analyzing it through data reduction, data display, and verification. The research focuses on understanding the kiai's leadership patterns in the context of modernization, revealing that this leadership is characterized by exemplary behavior (Uswah Hasanah), concern for subordinates, and a strong emphasis on service-oriented training. The findings contribute to the discourse on how pesantren can adapt traditional educational models to modern management practices while preserving their cultural and religious values.